2022
DOI: 10.15420/aer.2021.66
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management of Complex Ventricular Arrhythmias

Abstract: Percutaneous catheter ablation is an effective and safe therapy that can eliminate ventricular tachycardia, reducing the risks of both recurrent arrhythmia and shock therapies from a defibrillator. Successful ablation requires accurate identification of arrhythmic substrate and the effective delivery of energy to the targeted tissue. A thorough pre-procedural assessment is needed before considered 3D electroanatomical mapping can be performed. In contemporary practice, this must combine traditional electrophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“… 22 As discussed by Wiles et al, omnipolar voltage mapping may circumvent this issue, although clinical experience in humans remains limited. 4 Finally, bipolar voltage mapping alone is relatively non-specific for VT isthmuses and, therefore, may lead to excessive ablation, particularly in patients with large areas of scar. Anter et al showed in swine models of infarct-related VT that VT isthmuses occupied only 18% of the low-voltage endocardium (<1.5 mV), and that low voltage was 72% sensitive, but only 56% specific for VT isthmuses.…”
Section: Substrate Mappingmentioning
confidence: 99%
See 3 more Smart Citations
“… 22 As discussed by Wiles et al, omnipolar voltage mapping may circumvent this issue, although clinical experience in humans remains limited. 4 Finally, bipolar voltage mapping alone is relatively non-specific for VT isthmuses and, therefore, may lead to excessive ablation, particularly in patients with large areas of scar. Anter et al showed in swine models of infarct-related VT that VT isthmuses occupied only 18% of the low-voltage endocardium (<1.5 mV), and that low voltage was 72% sensitive, but only 56% specific for VT isthmuses.…”
Section: Substrate Mappingmentioning
confidence: 99%
“…At this point, operators may also consider ‘bail-out’ techniques targeting mid-myocardial substrate, such as bipolar ablation or low ionic irrigant ablation to generate larger ablation lesions. 4 , 42 …”
Section: Substrate Ablation With Selective Vt Induction: a Tailored A...mentioning
confidence: 99%
See 2 more Smart Citations